Kepuasan Masyarakat Terhadap Penyaluran Bantuan Sesajen (Banten) dari Pemerintah Provinsi Bali Melalui Program Atma Kerthi - Wijaya, Putu Yudy (Jurnal Bali Membangun Bali, 2022)
Purpose: This study aims to measure the level of community satisfaction as service users and improve the quality of public service delivery, especially Atma Kerthi services through the distribution of offerings (banten) which is carried out by the Government and Welfare Bureau of the Regional Secretariat of Bali Province. Design/methodology/approach: The research approach used is descriptive. The population in this study were recipients of offerings distributed by the Bali Provincial Government through the Atma kerthi Program in 2021, totaling 343 recipients. Furthermore, the sample size is determined by the approach of Morgan and Krejcie, in order to obtain a sample of 181 respondents. Data were collected through questionnaires, then tabulated, and analyzed using quantitative descriptive analysis. Findings: The composite community satisfaction index for the Bali Provincial Secretariat of Government and Welfare Bureau in the implementation of the Atma Kerthi program through the distribution of offerings is considered Good by the community and the quality of service is categorized B. Implications: Although on average, community satisfaction shows a good value, it is still necessary to pay attention to the value per element. One of them is regarding the amount of aid, as well as the system and mechanism for the distribution of aid to be evaluated to suit the needs of the community and meet the standard of excellent service.